The Crisis of Modernity and the Solution of Religious Spirituality: Analyzing Seyyed Hossein Nasr’s Perspective in Facing Global Challenges in the Contemporary Era - Hidayatulloh, Taufik (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2025)
The crisis of modern life often leads to confusion and spiritual emptiness in individuals, driven by the dominance of materialism and the marginalization of spiritual values. This condition causes modern humans to experience inner emptiness, confusion about the meaning of life, and difficulty in facing the complexities of life crises. This study aims to examine Seyyed Hossein Nasr’s views on religious spirituality as a response to the crisis experienced by modern humans. This research employs a descriptive qualitative approach with library study as the primary source. The data are analysed using logical reasoning both inductively and deductively to develop arguments regarding Nasr’s views on religious spirituality and the crisis of modern humanity. The findings of this study indicate that Nasr views religious spirituality, particularly the teachings of Sufism, as a path to overcoming spiritual dryness and the loss of meaning in life within modern society. Concepts such as the relationship between exoteric and esoteric, unity, the perfect human (Insan Kamil), and the importance of maintaining a balance between the external and internal dimensions are central to Nasr’s thought in addressing this crisis. The implication of this study is the necessity of reviving spiritual values within religion as a solution to the confusion and spiritual emptiness often experienced by modern humans.